Peningkatan Pemahaman Masyarakat Melalui Sosialisasi dan Informasi Persampahan di Permukiman Tempat Pembuangan Akhir Sampah (TPAS) Desa Sarimukti, Kabupaten Bandung - Maulana, Dickdick (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
The increase population and economic growth, currently still triggered the problem regarding waste management. Uncontrolled waste caused by human activity and industrialization, which then have an impact on the urban environment as beauty of the city. Therefore responsibilities of university as explained in Tridharma are education, research and community devotion. One of them is organizing a community devotion to women community around the landfill Sarimukti. The purpose of this community devotion is that people able to sort a garbage for developing science and welfaring of the community as expected to be healthy and provide alternative household waste management. The implementation of devotion community is using the method in the form of socialization/ education, followed by a question and answer, questionnaire and simulation. The conclusion of this activity is the increasing knowledge of the study of garbage, type of waste, and waste sources, waste management 3R (reduce, reuse, recycle), and the terms of a healthy house according to the health ministry. The results of that socialization is people already know the type of organic and inorganic waste, but to recycle waste people still do not understand about the reuse / recycling of garbage individually, although there is a communal garbage collection. How composting and sorting of waste in the household environment has not yet fullydone